Fractal Revolution: Unleashing Multi-Band Power in Compact ‎Patch Antennas for 5G and Beyond - Kadam , Sudhir; Mhetre, Hashada; Kadam , Prasad; Patil , Vishal; Gurav , Sachin; Mane , Snehal; Sutar, Sagar (International Journal of Basic and Applied Sciences, 2025)
This research presents the design and performance analysis of a dual-band microstrip patch antenna for wireless applications. The antenna, ‎fabricated on an FR-4 substrate, incorporates space-filling and self-similar properties to enhance performance. It operates in multiple frequency bands (2.2571 GHz, 3.8571 GHz, 5.0000 GHz, and 7.1714 GHz) with return loss values below -9 dB, indicating good impedance ‎matching. Simulation results demonstrate high radiation efficiency, stable group delay, and consistent radiation patterns across the operating ‎bands. The antenna’s peak gain exceeds 5 dB over a broad frequency range, occasionally reaching 8 dB. These characteristics make it suitable for various wireless applications, including WLAN, WiMAX, and sub-6 GHz 5G systems. The study concludes that the designed an‎tenna exhibits strong multiband performance with stable and efficient operation over the 2.2-7.1 GHz frequency band, making it viable for ‎integration in high-performance RF systems‎.